Effective Radiative Forcing in a GCM With Fixed Surface Temperatures. Issue 4 (22nd February 2021) - Andrews, Timothy; Smith, Christopher J.; Myhre, Gunnar; Forster, Piers M.; Chadwick, Robin; Ackerley, Duncan
Abstract: Effective radiative forcing (ERF) is evaluated in the ACCESS1.0 General Circulation Model (GCM) with fixed land and sea‐surface‐temperatures (SST) as well as sea‐ice. The 4xCO2 ERF is 8.0 W m −2 . In contrast, a typical ERF experiment with only fixed SST and sea‐ice gives rise to an ERF of only 7.0 W m −2 . This difference arises due to the influence of land warming in the commonly used fixed‐SST ERF experimental design, which results in: (i) increased emission of longwave radiation to space from the land surface (−0.45 W m −2 ) and troposphere (−0.90 W m −2 ), (ii) reduced land snow‐cover and albedo (+0.17 W m −2 ), (iii) increased water‐vapor (+0.49 W m −2 ), and (iv) a cloud adjustment (−0.26 W m −2 ) due to reduced stability and cloudiness over land (positive ERF) counteracted by increased lower tropospheric stability and marine cloudiness over oceans (negative ERF). The sum of these radiative adjustments to land warming is to reduce the 4xCO2 ERF in fixed‐SST experiments by ∼1.0 W m −2 . CO2 stomatal effects are quantified and found to contribute just over half of the land warming effect and adjustments in the fixed‐SST ERF experimental design in this model. The basic physical mechanisms in response to land warming are confirmed in a solar ERF experiment. We test various methods that have been proposed to account for land warming in fixed‐SST ERFs against our GCM results and discuss their strengths and weaknesses. Plain Language Summary: Radiative forcing measures the energy imbalance caused by anthropogenic activities (such as emissions of CO2, other greenhouse gases or aerosols) or natural events (such as volcanic eruptions). There are various definitions of radiative forcing, with the most commonly used being the "effective radiative forcing" which measures the energy imbalance after allowing for atmospheric temperatures, water vapor, and clouds to adjust to the forcing agent, while keeping surface conditions (specifically temperature) unchanged. However, in complex climate models it is difficult to prescribe land temperatures, so in practice effective radiative forcing (ERF) estimates are generally contaminated by the radiative effect of land temperature change and responses to it. Here, we quantify this effect for the first time, finding that for 4xCO2, the ERF is reduced by ∼1.0 W m −2 (∼14%) in a typical climate model ERF experiment due to land warming and its impact on temperatures, water‐vapor, clouds, and surface albedo. Key Points: 4xCO2 effective radiative forcing is ∼1 W m −2 less in a typical General Circulation Model ERF experiment with fixed sea‐surface‐temperature compared to an ERF experiment with fixed SST and land temperatures This is due to the influence of land warming on temperature, lapse‐rate, water‐vapor, surface albedo, and clouds in the fixed‐SST experiment Previous methods used to account for land warming in fixed‐SST ERF experiments are evaluated